In Silico and In Vivo: Evaluating the Therapeutic Potential of Kaempferol, Quercetin, and Catechin to Treat Chronic Epilepsy in a Rat Model - Ahmed, Hammad; Khan, Mahtab Ahmad; Ali Zaidi, Syed Awais; Muhammad, Sajjad (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, alternative therapies are gaining popularity in the treatment of epilepsy. The present study aimed to find out the antiepileptic potential of quercetin, catechin, and kaempferol. In vivo and in silico experiments were conducted to investigate their therapeutic potential. 25 mg/kg/day of pentylenetetrazole was administered for 4 weeks after epilepsy was induced in the rats; this was followed by the behavioral studies and histological analysis of rat brain slices. Binding affinities of kaempferol, quercetin, and catechin were assessed by performing in silico studies. Kaempferol, quercetin, and catechin were found to have the highest binding affinity with the synaptic vesicle 2A (SV2A) protein, comparable to standard levetiracetam (LEV). The mRNA levels of SV2A, as well as the expression of TNF, IL 6, IL 1 beta, NFkB, IL 1Ra, IL 4, and IL 10, were investigated using qPCR. Our results indicate for the first time that SV2A is also a transporter of understudied phytoflavonoids, due to which a significant improvement was observed in epileptic parameters. The mRNA levels of SV2A were found to be significantly elevated in the PF-treated rats when compared with those of the control rats with epilepsy. Additionally, downregulation of the pro-inflammatory cytokines and upregulation of the anti-inflammatory cytokines were also noted in the PF-treated groups. It is concluded that kaempferol, quercetin, and catechin can effectively decrease the epileptic seizures in our chronic epilepsy rat model to a level that is comparable to the antiepileptic effects induced by levetiracetam drug.